6x-2=y

Simple and best practice solution for 6x-2=y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2=y equation:


Simplifying
6x + -2 = y

Reorder the terms:
-2 + 6x = y

Solving
-2 + 6x = y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 6x = 2 + y

Combine like terms: -2 + 2 = 0
0 + 6x = 2 + y
6x = 2 + y

Divide each side by '6'.
x = 0.3333333333 + 0.1666666667y

Simplifying
x = 0.3333333333 + 0.1666666667y

See similar equations:

| 5x^2+12x+3= | | -2x-17=-7 | | x/20 | | 10(x-2)=5(x+8) | | 6x+2x=3x+3 | | 14=4x-3 | | 3x-2=3x+1 | | 6-5x+2=3x-12+2x | | 2(1-7x)+4=8 | | 35x^5/7x^2 | | 2x+10=6x+8 | | x^2-8+8=0 | | -16x-5=3x^2 | | 16x^16=9 | | 3x^5/7x^2 | | 7x+4y+4z-4x+2z-5y= | | -5x/6=-4/5 | | 8x^4-8x^2-1=0 | | tan(9.8*x)=1.74 | | SolveR=M(1+n)forn | | 2x+10+6x+8=180 | | 6-5x=1/2 | | 1.2*x=3 | | 185+z^2+18z+81=9(45+25-10z+z^2) | | -9v-5=95 | | 4log(x+2)=7 | | (-0.5b+-0.25c)+(1.3+-0.83c)+c=-2 | | (ax+b)(bx+a)=10x^2+cx+10 | | 9(x-5)+6=-39 | | -(-3+x)-(7-x)-3=-(2-x)+(-x)+1 | | 5x-(2x+9)=6x-36 | | 2z^2-27+91=0 |

Equations solver categories